His Majesty King George V. Death of II (Colonial Letters and the Contact of Knowledges, 1936)
This file contains second set of colonial letters on the death of George V.
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies